Probabilistic load forecast by using Markov chain - Harmen, Kevin (2017)
In this modern life society, the need for a stable supply of electricity is undeniably true. The development of this era brought to a rapid demand of electricity in all part of the human activities. The demand of electricity supply grows all over the world rises, and required to be supplied to places where electricity was a scarce resource. In the drive of electrical demand, the requirements for electricity transmission from generating stations to end-users are getting higher and transmission is required to be installed. In the high demand of power transmission from stations to the users, the stability and dependability of the transmission network is required to fulfil the standards. In the preparation of the systems, risk assessment of the designed transmission network has to be performed to observe the capability of the system. The risk assessment counts for the Expected Load Not Served (ELNS) of the system, by considering the components characteristics in the transmission system. This study aims to obtain the ELNS of a transmission system, based on the probability of components breakdown rate in the system. In this study, Monte Carlo Simulation would be performed as this study deals with a number of uncertainties and assumptions. With the assistance of MATLAB software and programming, the author aimed to get the expected value of the required objective with a considerable confidence.